Os profissionais da Estratégia de Saúde da Família (ESF) e a construção de sentidos sobre adolescência - Fonseca, Débora Cristina (2008)
The aim of this study was to understand the meanings of adolescence built by health professionals who integrate the Family Health Strategy (Estratégia de Saúde da Família ESF) in a city in the interior of São Paulo State. It was an attempt to contextualize and discuss how the practice with adolescents has been conceived, thought and developed in health contexts and in the formation of doctors and nurses. These professionals have always been present in Family Health teams. The hypothesis adopted was that the naturalizing, universal and pathologic conceptions about adolescence are predominant. They represent an important element in the definition of health policies and practices applied to that population and, consequently, in the lack of effectiveness of these proposals. The theoretical and methodological reference of this study belongs to Social-historical Psychology, in the perspective of Vigotski (1995), Bock & Aguiar (2003) and Aguiar & Ozella (2006). This research was supported on the assumption that any concept or meaning is built in the relationship among men mediated by their objective conditions of life, social and historical realities as well as their symbolization process. Thus, it is a qualitative research, which used the semi-structured interview as a privileged instrument. The analysis was based on four interviews made with health professionals (doctors and nurses). The material collected was organized in pre-indicators, indicators and meaning cores. As a result, the meanings built about Family Health Strategy in integrality and care perspectives were emphasized. However, the discourses about the work routine pointed out to a fragmented practice, which arose from an organizational model of health services. The meanings built by the professionals about adolescence and their work with this group highlighted the predominant conception. It was defined as naturalizing, universal and pathological and also included the invisibility of the adolescent subjects in that context, confirming their inexistence in the professional formation. On the other hand, these professionals recognize the need for overcoming the dominant model. Anyway, they have shown difficulties in finding out ways to modify their practices